Alarming antibody evasion properties of rising SARS-CoV-2 BQ and XBB subvariants - Wang, Qian; Iketani, Sho; Li, Zhiteng; Liu, Liyuan; Guo, Yicheng; Huang, Yiming; Bowen, Anthony D.; Liu, Michael; Wang, Maple; Yu, Jian; Valdez, Riccardo; Lauring, Adam S.; et al. (Cell, 2023)
The BQ and XBB subvariants of SARS-CoV-2 Omicron are now rapidly expanding, possibly due to altered antibody evasion properties deriving from their additional spike mutations. Here, we report that neutralization of BQ.1, BQ.1.1, XBB, and XBB.1 by sera from vaccinees and infected persons was markedly impaired, including sera from individuals boosted with a WA1/BA.5 bivalent mRNA vaccine. Titers against BQ and XBB subvariants were lower by 13- to 81-fold and 66- to 155-fold, respectively, far beyond what had been observed to date. Monoclonal antibodies capable of neutralizing the original Omicron variant were largely inactive against these new subvariants, and the responsible individual spike mutations were identified. These subvariants were found to have similar ACE2-binding affinities as their predecessors. Together, our findings indicate that BQ and XBB subvariants present serious threats to current COVID-19 vaccines, render inactive all authorized antibodies, and may have gained dominance in the population because of their advantage in evading antibodies. [Display omitted] •BQ.1, BQ.1.1, XBB, and XBB.1 are the most resistant SARS-CoV-2 variants to date•Serum neutralization was markedly reduced, including with the bivalent booster•All clinical monoclonal antibodies were rendered inactive against these variants•The ACE2 affinity of these variants were similar to their parental strains Recent BQ and XBB subvariants of SARS-CoV-2 demonstrate dramatically increased ability to evade neutralizing antibodies, even those from people who received the bivalent mRNA booster or who are immunized and had previous breakthrough Omicron infection. Additionally, both BQ and XBB are completely resistant to bebtelovimab, meaning there are now no clinically authorized therapeutic antibodies effective against these circulating variants.